Hybrid Entrepreneurship - Folta, Timothy B.; Delmar, Frédéric; Wennberg, Karl (Management Science, 2010)
In contrast to previous efforts to model an individual's movement from wage work into entrepreneurship, we consider that individuals might transition incrementally by retaining their wage job while entering into self-employment. We show that these hybrid entrepreneurs represent a significant share of all entrepreneurial activity. Theoretical arguments are proposed to suggest why hybrid entrants are distinct from self-employment entrants, and why hybrid entry may facilitate subsequent entry into full self-employment. We demonstrate that there are significant theoretical and empirical consequences for this group and our understanding of self-employment entry and labor market dynamics. Using matched employee–employer data over eight years, we test the model on a population of Swedish wage earners in the knowledge-intensive sector.